Innovation in near-surface geophysics instrumentation, application, and data processing methods - Persico, Raffaele 1969-; Piro, Salvatore 1954-; Linford, Neil (Elsevier, 2019)
Innovation in Near-Surface Geophysics: Instrumentation, Application, and Data Processing Methods offers an advanced look at state-of-the-art and innovative technologies for near surface geophysics, exposing the latest, most effective techniques in an accessible way. By addressing a variety of geophysical applications, including cultural heritage, civil engineering, characteristics of soil, and others, the book provides an understanding of the best products and methodologies modern near surface geophysics has to offer. It proposes tips for new ideas and projects, and encourages collaboration across disciplines and techniques for the best implementation and results. Clearly organized, with contributions from leaders from throughout geophysics, Innovation in Near-Surface Geophysics is an important guide for geophysicists who hope to gain a better understanding of the tools and techniques available.Addresses a variety of applications in near-surface geophysics, including cultural heritage, civil engineering, soil analysis, and more. Provides insights into available products and techniques and offers suggestions for future developments